PENGARUH MODEL PEMBELAJARAN SURVEY, QUESTION, READ, RECITE REVIEW (SQ3R) DAN KEMAMPUAN BERPIKIR KRITIS TERHADAP HASIL BELAJAR PESERTA DIDIK SMA - Fahmawati, Fahriyah; Rusdi, Rusdi; Komala, Ratna (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2017)
The development of learning in the 21st century, requires students to have the competency that can support in the development of the times. competency is one of them is the ability to think critically. Students must have this competency in order to solve problems faced such as environmental pollution problems. The problem of environmental pollution is one part of biology, by collaborating SQ3R model that has advantages for cooperation between students and students enggagment. is expected to contribute greatly to students able to solve problems. Quasi Research This experiment uses two way anova design (2x2 factorial). This research was conducted at SMA Negeri 1 Tambun Utara in May-June 2017. The result data showed normal and homogeneous values (p> 0.05) with 140 samples. Result of research using two way anova test got data that p value = 0.000, mean p <0.05 (reject H0). The conclusion is that (1) there is influence of SQ3R model to learning outcomes, (2) there is influence of critical thinking to learning result, and (3) there is interaction between SQ3R and critical thinking to result of learning.